2021
DOI: 10.3390/cancers13184686
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 Protein Interactions in Prostate and Ovary Cancer Models Reveal Links to RNA Processing and Ribosome Biogenesis through NuRD, THOC and Septin Complexes

Abstract: This study reports the HMGB1 interactomes in prostate and ovary cancer cells lines. Affinity purification coupled to mass spectrometry confirmed that the HMGB1 nuclear interactome is involved in HMGB1 known functions such as maintenance of chromatin stability and regulation of transcription, and also in not as yet reported processes such as mRNA and rRNA processing. We have identified an interaction between HMGB1 and the NuRD complex and validated this by yeast-two-hybrid, confirming that the RBBP7 subunit dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…This is because metabolic reprogramming in cancer cells or embryo/ stem cells is often accompanied by many epigenetic alterations that require a large number of transcriptional regulators, that incidentally drive the upregulation of RBBP4/7. Thus, some researchers believe that RBBP4/7 can be used as a marker for cancer (Barreiro-Alonso et al, 2021;Khateb et al, 2021). Interestingly, just as RBBP4/7 is often overlooked in the study of epigenetic complexes implicated in cancer, research on RBBP4/7 in cancer also tends to overlook the complex in which its true functional effects reside (Shou et al, 2021).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because metabolic reprogramming in cancer cells or embryo/ stem cells is often accompanied by many epigenetic alterations that require a large number of transcriptional regulators, that incidentally drive the upregulation of RBBP4/7. Thus, some researchers believe that RBBP4/7 can be used as a marker for cancer (Barreiro-Alonso et al, 2021;Khateb et al, 2021). Interestingly, just as RBBP4/7 is often overlooked in the study of epigenetic complexes implicated in cancer, research on RBBP4/7 in cancer also tends to overlook the complex in which its true functional effects reside (Shou et al, 2021).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…In prostate cancer, RBBP7 interacts directly with HMGB1, which allows HMGB1 to participate in the RNA metabolic process and thus promotes cancer cell proliferation and differentiation, making the prognosis of patients with high HMGB1 expression worse (Barreiro-Alonso et al, 2021). However, RBBP7 can also bind to HNF1B as part of multiple transcriptional repressor complexes, thereby inhibiting EMT in prostate cancer via direct suppression of EMT factor SLUG expression, except that HNF1B is often repressed by EZH2 overexpression (Wang et al, 2020).…”
Section: Prostate Cancermentioning
confidence: 99%
“…Cai et al ( 159 ) showed that there is a physical interaction between the tumor suppressor gene EAF2 (encoding ELL associated factor 2) and RBBP4/7, where their overexpression induces cell death in LNCaP prostate cancer cells. High RBBP4/7 expression in prostate adenocarcinoma is also linked to shorter progression-free survival, with RBBP7 interacting with high mobility group box 1 to regulate RNA processing ( 160 ). Furthermore, overexpression of RBBP7 suppresses SLUG1/EMT in DU145 cells and exerts tumor suppressive functions in presence of hepatocyte nuclear factor 1β ( 161 ).…”
Section: Expression and Function Of Rbbp4/7 In Diseasesmentioning
confidence: 99%
“…To extend the number of targets detected in the Y2H interactomes, we also carried out a HMGB1-interactome analysis approach based on immunoprecipitation (IP) and mass spectrometry (MS) in prostate and ovary cancer cell lines. The corresponding HMGB1 nuclear interactomes were clearly enriched in mRNA and rRNA processing factors [152]. The interaction of HMGB1 with the subunit Rbbp7 of the Nucleosome Remodeling (NuRD) complex was validated and other subunits of this complex were also identified in the IPs, including the histone deacetylases HDAC1 and HDAC2 [152].…”
mentioning
confidence: 91%
“…The corresponding HMGB1 nuclear interactomes were clearly enriched in mRNA and rRNA processing factors [152]. The interaction of HMGB1 with the subunit Rbbp7 of the Nucleosome Remodeling (NuRD) complex was validated and other subunits of this complex were also identified in the IPs, including the histone deacetylases HDAC1 and HDAC2 [152]. The Upstream binding factor (UBF) is responsible for the recruitment of the RNA PolI pre-initiation complex required for rRNA transcription.…”
mentioning
confidence: 97%